2015
DOI: 10.1002/jbm.b.33413
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired synthesis of hydroxyapatite nanocrystals in the presence of collagen and l‐arginine: Candidates for bone regeneration

Abstract: This work aims at the bioinspired synthesis of hydroxyapatite (HAp) crystals in the presence of both collagen and l-arginine, in an effort to obtain a homogeneous hybrid material, having a bone-like nanostructure. Collagen (Col) is the most commonly utilized protein in most species of life, while L-arginine (Arg) encourages cell attachment, proliferation, and differentiation on HAp surfaces. Transmission electron microscopy, X-ray diffraction and Fourier transform-infrared spectroscopy were used to analyze sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Hydroxyapatite is the major inorganic component of human bone mineral . The tHA synthesized in our study displayed a plate‐like structure, which shows greater similarity to the morphology of natural hydroxyapatite in bone tissue than to rod‐like traditional HA . X‐ray photoelectron spectrometry showed that tHA and traditional HA displayed the same main atomic elements (oxygen, carbon, calcium, and phosphorus), which indicated that they both have the basic chemical characteristic of hydroxyapatite.…”
Section: Discussionmentioning
confidence: 62%
“…Hydroxyapatite is the major inorganic component of human bone mineral . The tHA synthesized in our study displayed a plate‐like structure, which shows greater similarity to the morphology of natural hydroxyapatite in bone tissue than to rod‐like traditional HA . X‐ray photoelectron spectrometry showed that tHA and traditional HA displayed the same main atomic elements (oxygen, carbon, calcium, and phosphorus), which indicated that they both have the basic chemical characteristic of hydroxyapatite.…”
Section: Discussionmentioning
confidence: 62%
“…In comparison, M2-like macrophages did not significantly increase until a later stage of OTM (between days 21 and 28). As production of M2-phenotype markers such as Arg-1 can promote bone formation, this switch may be important for the cessation of bone resorption and initiation of tissue repair 29 , 30 . However, whether macrophage polarization directly influences OTM is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It was proved that the best results in the integration with the bone tissue just demonstrated those materials that are comprised of the analogue of the mineral compound in the bone human tissue -calcium hydroxyapatite (HAP) and organic matrix used for the improvement of the reparative processes, increase in the resorption rate and strength [1,3,[7][8][9]. Complex materialsbiocomposites, elaborated on the basis of calcium hydroxyapatite, collagen, chitosan or any other biodegradable organic matrix have a lot of advantages for dental applications implying the control of their bioactivity and resorption rate [2,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…The generally accepted trend for reducing the risks of rejection of the xenogenic samples involves the incorporation of the medical preparations or some organic agents [7,9,13]. However, the rate of biodegradation and osseointegration of synthetic samples can be determined based on their surface characteristics as well as performed preliminary treatment including the side action effect of introduced agents.…”
Section: Introductionmentioning
confidence: 99%